ARCHIPELAGO - Aplikasi Augmented Reality (AR) Pengenalan Tokoh - Tokoh Pahlawan Nasional Indonesia Dengan Metode Image Tracking Berbasis Android: ARCHIPELAGO - Augmented Reality (AR) Application Recognition Of Indonesian National Heroes With Image Tracking Method Based On Android - Yohanes Alfian Richiansyah; Julius Panda Putra Naibaho; Parma Hadi Rantelinggi (Universitas Papua, 2022)
The history of the struggle of Indonesian national heroes is unknown to the majority of people and students.Users may find it simpler to learn the history of the introduction of national heroes if the application of hero figures is used. Utilizing the Waterfall development model, research is conducted using R&D.Utilizing UML tools, use cases, activity diagrams, and sequence diagrams, as well as vuforia unity, the development methodology is supported. The functional average - average answers for users based on standard usageIn the meantime, 25 out of 30 respondents stated that the display color selection in the application was in accordance with the eligibility standards.The application's overall design view is 95% related to the application's design.